Reformulation Of Statistical Data Sources: Big Data New Data Sources Supporting Future Official Statistics? - Ardiansyah, Ari; Ilyas, Amir; Haeranah, Haeranah (Pusat Publikasi Nusantara, 2023)
Big Data is the new oil. The real issue of the development of information technology is the existence of Big Data. Big Data is very important, talking about Big Data not only touches the issue of how big data you have, but what can be done with the data. The high cost of Big Data access is inversely proportional to the collection of data through surveys or censuses for free. analysis of the application of efficiency theory in an economic approach in imposing access costs to statistical activities, knowing the impact of imposing Big Data access fee tariffs, knowing the potential of Big Data as a supporter of official statistics in the future, what are the obstacles and solutions in implementing it. The preparation of this paper is juridical-empirical research with the nature of descriptive research with an economic law approach. Big Data is managed for different purposes using different systems and methods and not necessarily using statistical rules. The implementation of Big Data as a new data source is carried out through a combination of data sources. The imposition of Big Data access fees as a source of data supporting official statistics causes low utilization of Big Data as a new data source. The information technology revolution makes Big Data has the potential to complement, replace, improve, add, and improve the composition of existing statistical data sources, and produce more timely outputs. Difficult access and high costs for data collection are major obstacles. Therefore, it needs to be supported by legal instruments that facilitate its implementation in Indonesia. One is the reformulation of existing regulations that make it easier for basic statistical organizations to obtain such data sources for free and use only in the national interest